Recycled materials for sublayers - Richard Svoboda; Dana Hubáčková; Jan Valehrach (Acta Polytechnica CTU Proceedings, 2023)
The article focuses on the recycled materials used in sleeper substructure. In the introduction, it summarizes the requirements for bearing layers of railway substructure and recycling of waste construction materials. The article presents the materials on which laboratory tests have been carried out and discusses in detail the most perspective – recycled concrete. For concrete recyclate, the article describes the results of laboratory tests – sieve analysis, determination of optimum moisture, and determination of bearing capacity using California bearing ratio, Immediate bearing index and Static deformation modulus.